Ocena škodljivih posledic pitja alkohola na Dolenjskem in v ostali Sloveniji - Radešček, Darja (Zdravniški vestnik, 2002)
Background. Dolenjska is a region with well developed viniculture and spirits production. The analysis of the mortality, premature mortality, hospitalization and temporary absence from work attributed to alcohol in Dolenjska in comparison to those in the other part of Slovenia was performed. Methods. Data source on mortality, premature mortality, hospitalization and temporary absence from work was national statistics of the Institut of Public Health of the Republic of Slovenia and of the Health Insurance Institut of Slovenia. Statistical data were collected in accordance with diagnoses and agelimits defined by the metodology of the Centers for Disease Control in USA for each gender separately (1991-1996). Alcohol-related mortality, premature mortality, hospitalization and temporary absence from work were calculated using in the USA established alcohol attributable fractions for each disease or injury with the exception of the cirrhosis of the liver, for which the known Slovene alcohol attributable fractions for each disease or injury with the exception of the cirrhosis of the liver, for which the known Slovene alcohol attributable fraction exists. Results. Selected health indicators are pointing important differences for men and partly for women in Dolenjska in comparison to the rest of Slovenia. In Dolenjska there are 12.0% of deaths, 23% of premature mortality, 6.2% of hospitalizations and 3.4% of temporary absence from work attributed to alcohol. In the other part of Slovenia there are 9.6% of deaths, 19.4% of premature mortality, 5.3% of hospitalizations and3.4% of temporary absence from work attributed to alcohol. Conclusions. There is a need to build up national alcohol policy. It must be based upon measures for reducing alcohol supply and demand, early detecting and preventing harmful drinking and treatment of the dependance on alcohol. (Abstract trunacted at 2000 characters).
Keywords: Absenteeism; Absentizem; Alcohol drinking; Alcoholism; alkohol; Alkohol, pitje; Alkoholizem; Dolenjska; Hospitalizacija; Hospitalization; Lower Carniola; mortaliteta; Mortality; pitje; škodljivost